Clustering Performa Pemain Basket Berdasarkan Posisi dan Statistik Pemain Menggunakan Metode Fuzzy c-Means - Gregorry, Febrianus; Nataliani, Yessica (Jurnal Transformatika, 2022)
Satya Wacana Saints Salatiga is one of the professional teams that compete in Indonesian Basketball League (IBL). Player evaluation has been done as an effort to maintain the quality and performance of all players which can be used as team records. They can also make a couple of improvements within the team for the next season. Classifying the players performance by using the fuzzy c-means algorithm is the aim of this research. Player performance is determined based on five kinds of player statistical criteria, namely points, assists, blocks, rebounds, and steals from each position. The assessment carried out in this study is using weighting criteria for each position. The grouping by weighting aims to get the highest to the lowest scores from each player so that they can be grouped into three performance groups; good, moderate, and poor performance. The results of the fuzzy c-means grouping of 15 players of the Satya Wacana Saints Salatiga team with weighting obtained three players with good performance, five players with moderate performance, and seven players with poor performance. Meanwhile, the results of the fuzzy c-means grouping without weighting obtained five players with good performance, three players with moderate performance, and seven players with poor performance. Both grouping results are compared with the actual performance data. The result of the comparison was found that the grouping with weighting resulted in an accuracy rate of 100% and the grouping without weighting resulted in an accuracy rate of 86.67%. Grouping with weighting on different statistical values for each player position has an effect on player performance. Each player position has different strengths in scoring points, assists, rebounds, steals, block shoots, and field goals.